Physicochemical Properties of Edible Films Prepared from Arrowroot (Maranta arundinacea) Starch Extracted through Microwave-Assisted Extraction (MAE) - Mimi Harni; Rilma Novita; Rivo Yulse Viza; Yenni Muchrida (Green Engineering Society, 2025)
Plastic is a commonly used packaging material due to its cheap and wide availability, especially in the food industry. However, plastic is non-biodegradable, leading to a serious problem to the environment from its widespread use. Using starch-based edible films as an alternative to plastic packaging offers a solution to this problem. As opposed to conventional methods of starch extraction for edibles, modern methods such as microwave-assisted extraction (MAE) can improve the functional properties of starchThis research aimed to determine the physicochemical properties of edible films from starch extracted through MAE. The study used a completely randomized design (CRD) with three treatments based on the amount of added starch, namely, Treatment A (3%), Treatment B (4%), and Treatment C (5%). The results from these treatments were compared against control (without MAE). Observations were conducted in triplicate, including parameters such as solubility, thickness, water holding capacity (WHC), oil holding capacity (OHC), and water content. Treatment A (3%) was found to be the best treatment, with a solubility of 76.55%, a thickness of 0.243 mm, a WHC of 38.56%, an OHC of 36.67%, and a water content of 13.79%.